Alterations of N‐3 Polyunsaturated Fatty Acid‐Activated K2P Channels in Hypoxia‐Induced Pulmonary Hypertension. (27th June 2013) - Nielsen, Gorm; Wandall‐Frostholm, Christine; Sadda, Veeranjaneyulu; Oliván‐Viguera, Aida; Lloyd, Eric E.; Bryan, Robert M.; Simonsen, Ulf; Köhler, Ralf
Abstract: Polyunsaturated fatty acid (PUFA)‐activated two‐pore domain potassium channels (K2P ) have been proposed to be expressed in the pulmonary vasculature. However, their physiological or pathophysiological roles are poorly defined. Here, we tested the hypothesis that PUFA‐activated K2P are involved in pulmonary vasorelaxation and that alterations of channel expression are pathophysiologically linked to pulmonary hypertension. Expression of PUFA‐activated K2P in the murine lung was investigated by quantitative reverse‐transcription polymerase chain reaction (qRT‐PCR), immunohistochemistry (IHC), by patch clamp (PC) and myography. K2P ‐gene expression was examined in chronic hypoxic mice. qRT‐PCR showed that the K2P 2.1 and K2P 6.1 were the predominantly expressed K2P in the murine lung. IHC revealed protein expression of K2P 2.1 and K2P 6.1 in the endothelium of pulmonary arteries and of K2P 6.1 in bronchial epithelium. PC showed pimozide‐sensitive K2P ‐like K + ‐current activated by docosahexaenoic acid (DHA) in freshly isolated endothelial cells as well as DHA‐induced membrane hyperpolarization. Myography on pulmonary arteries showed that DHA induced concentration‐dependent instantaneous relaxations that were resistant to endothelial removal and inhibition of NO and prostacyclin synthesis and to a cocktail of blockers of calcium‐activated K + channels but were abolished by high extracellular (30 mM) K + ‐concentration. Gene expression and protein of K2P 2.1 were not altered in chronic hypoxic mice, while K2P 6.1 was up‐regulated by fourfold. In conclusion, the PUFA‐activated K2P 2.1 and K2P 6.1 are expressed in murine lung and functional K2P ‐like channels contribute to endothelium hyperpolarization and pulmonary artery relaxation. The increased K2P 6.1‐gene expression may represent a novel counter‐regulatory mechanism in pulmonary hypertension and suggest that arterial K2P 2.1 and K2P 6.1 could be novel therapeutic targets.